ANALISIS KASUS MONOPOLI DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Damisa, Arti (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2016)
AbstractMonopoly is the ruler over the production and or marketing of goods and or the use of certain services by one business actor or a group of business actors. In Islam, anyone can do business regardless of whether he is the sole seller (monopoly) or there is another seller. Keep a stock of goods for inventory purposes was not prohibited in Islam. Monopolistic market structure is not an unclean thing if the situation in the case of natural monopoly. But what is not allowed is monopolistic behavior (mopolistic behavior) as set prices above the market price in order to attract as many benefits or decrease the quantity of production in order to raise the price high.Keywords: Monopoly, Price, Positive Law, Islamic Law